2020
DOI: 10.1016/j.jecp.2019.104781
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in lexical processing efficiency and vocabulary in toddlers: A longitudinal investigation

Abstract: Research on infants' online lexical processing by Fernald, Perfors, and Marchman (2006) revealed substantial individual differences that are related to vocabulary development, such that infants with better lexical processing efficiency show greater vocabulary growth across time. Although it is clear that individual differences in lexical processing efficiency exist and are meaningful, the theoretical nature of lexical processing efficiency and its relation to vocabulary size is less clear. In the current study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
2
15
0
1
Order By: Relevance
“…Since socioeconomic status (SES) has been shown to be associated with both variation in input and vocabulary development (Bergelson et al, 2019; Hart & Risley, 1995; Hoff, 2003; Rowe, 2012), it is important to acknowledge that our results may not generalize fully to other populations. Interestingly, however, we note that even within more narrow SES bands we see large individual differences in both input and vocabulary development (Donnelly & Kidd, 2020; Weisleder & Fernald, 2013). Data on participant ethnicity were not collected, although the sample was representative of the Canberra population, which is predominantly of white, Anglo‐Celtic origin (approx.…”
Section: Methodsmentioning
confidence: 80%
“…Since socioeconomic status (SES) has been shown to be associated with both variation in input and vocabulary development (Bergelson et al, 2019; Hart & Risley, 1995; Hoff, 2003; Rowe, 2012), it is important to acknowledge that our results may not generalize fully to other populations. Interestingly, however, we note that even within more narrow SES bands we see large individual differences in both input and vocabulary development (Donnelly & Kidd, 2020; Weisleder & Fernald, 2013). Data on participant ethnicity were not collected, although the sample was representative of the Canberra population, which is predominantly of white, Anglo‐Celtic origin (approx.…”
Section: Methodsmentioning
confidence: 80%
“…RTs were calculated following the procedure from Fernald, Perfors, and Marchman (2006): On the trials in which participants were looking to the distracter image prior to the onset of the target word, we calculated the duration between the onset of the target word and the participant's first 100 ms fixation on the target between 200 and 1800 ms post onset. While previous research has extracted RTs after 300 ms, these studies have typically been done with younger children (Donnelly & Kidd, 2020; Fernald et al., 2006), and we found that doing so dropped an unacceptable number of trials (347 trials or 25% of possible trials, compared to 171% or 12% of possible trials when 200 ms was used). The proportion of looks to the target image was calculated after the onset of the target word.…”
Section: Methodsmentioning
confidence: 54%
“…Taken with these findings, our results place an important constraint on the large current research focused on lexical processing as a predictor of individual differences in language outcomes (e.g., Egger, Rowland, & Bergmann, 2020; Fernald et al., 2006; Marchman & Fernald, 2008). An important conceptual limitation of this work is that it is conducted largely without a working theoretical model of the lexicon (see Donnelly & Kidd, 2020); it implicitly assumes a largely unidirectional and linear relationship between knowledge and lexical processing speed (i.e., faster RTs are always better). Our results, as well as the literature described above, indicate that there are subtle item‐based influences on lexical access that are inconsistent with this assumption but which fit with what we know about adult lexical access.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations